Neonatal carnitine concentrations in relation to gestational age and weight - Loek L. Crefcoeur (JIMD Reports, 2020)
Abstract Background Free carnitine has been measured in the Dutch newborn screening (NBS) program since 2007 with a referral threshold of ≤5 μmol/L, regardless of gestational age or birthweight. However, several studies suggest that carnitine concentrations may depend on gestational age and birthweight. We evaluated differences in postnatal day‐to‐day carnitine concentrations in newborns based on gestational age (GA) and/or weight for GA (WfGA). Methods A retrospective study was performed using data from the Dutch NBS. Dried blood spot (DBS) carnitine concentrations, collected between the 3rd and 10th day of life, of nearly 2 million newborns were included. Individuals were grouped based on GA and WfGA. Median carnitine concentrations were calculated for each group. Mann‐Whitney U tests, and chi‐square tests were applied to test for significant differences between groups. Results Preterm, postterm, and small for GA (SGA) newborns have higher carnitine concentrations at the third day of life compared to term newborns. The median carnitine concentration of preterm newborns declines from day 3 onwards, and approximates that of term newborns at the sixth day of life, while median concentrations of postterm and SGA newborns remain elevated at least throughout the first 10 days of life. Carnitine concentrations ≤5 μmol/L were found less frequently in SGA newborns and newborns born between 32 and 37 weeks of gestation, compared to term newborns. Conclusions Median carnitine concentrations in NBS DBS vary with day of sampling, GA, and WfGA. It is important to take these variables into account when interpreting NBS results..